2014
DOI: 10.1523/jneurosci.1373-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Eukaryotic Translation Initiation Factor 2B Activity Specifically in Oligodendrocytes Reproduces the Pathology of Vanishing White Matter Disease in Mice

Abstract: Vanishing white matter disease (VWMD) is an inherited autosomal-recessive hypomyelinating disease caused by mutations in eukaryotic translation initiation factor 2B (eIF2B). eIF2B mutations predominantly affect the brain white matter, and the characteristic features of VWMD pathology include myelin loss and foamy oligodendrocytes. Activation of pancreatic endoplasmic reticulum kinase (PERK) has been observed in oligodendrocytes in VWMD. PERK activation in response to endoplasmic reticulum stress attenuates eIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 47 publications
1
53
1
Order By: Relevance
“…PERK activation decreases eIF2B activity via phosphorylation of the initiation factor eIF2, while in VWM, eIF2B activity is affected by mutations in eIF2B subunit genes and not invariably decreased (9). Our results, especially the coculture data, contradict the conclusion of Lin et al (52).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…PERK activation decreases eIF2B activity via phosphorylation of the initiation factor eIF2, while in VWM, eIF2B activity is affected by mutations in eIF2B subunit genes and not invariably decreased (9). Our results, especially the coculture data, contradict the conclusion of Lin et al (52).…”
Section: Discussioncontrasting
confidence: 99%
“…This mutant mouse had a normal lifespan, subtle motor impairment at most, and white matter abnormalities that only became manifest after experimental demyelination (30,53). Using transgenic mice that allow activation of PERK specifically in oligodendrocytes, Lin et al (52) concluded that PERK activation in oligodendrocytes plays a cell-autonomous role in VWM pathology. PERK activation decreases eIF2B activity via phosphorylation of the initiation factor eIF2, while in VWM, eIF2B activity is affected by mutations in eIF2B subunit genes and not invariably decreased (9).…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of neuropathology-associated eIF2B mutant alleles suggests critical roles of eIF2B subunits in regulating homeostasis and myelin formation function of glial cells in the mammalian brain (Lin et al 2014). We also note that the eIF2B regulatory d-subunit has been identified as the molecular target of the drug ISRIB that renders mammalian neurons refractory to eIF2a phosphorylation to enhance memory formation (Sekine et al 2015;Sidrauski et al 2015).…”
Section: Resultsmentioning
confidence: 75%
“…Mouse models that reproduce the characteristics of VWMD have been difficult to produce (Lin et al, 2014b). Point mutations in eIF2B reproduce some white matter deficits but to a much milder degree than seen in VWMD.…”
Section: Er Stress In Vanishing White Matter Diseasementioning
confidence: 99%
“…Point mutations in eIF2B reproduce some white matter deficits but to a much milder degree than seen in VWMD. While the role that ER stress plays in the phenotype of these mouse models has not been examined (Geva et al, 2010), a recent study using transgenic mice provides evidence for a role of ER stress in VWMD (Lin et al, 2014b). PLP/Fv2E-PERK transgenic mice allow for oligodendrocyte-specific expression of a chimeric protein that contains the luminal eIF2α kinase domain of PERK fused to a small molecule-driven artificial dimerizing domain.…”
Section: Er Stress In Vanishing White Matter Diseasementioning
confidence: 99%